Molecular Screening of Adhesion Proteins Genes in Staphylococcus aureus Strains Isolated from Different Clinical Infections in Baghdad City and Identification of Their Relationship with Some Virulence Factors - Al Ani, Aalaa Theyab Ahmed; Al Meani, Safaa Abed Lateef (Al-Nahrain Journal of Science, 2018)
The first step to achieve Staphylococcus aureus infections is the adhesion process that is mediated by proteins belong to the microbial surface component recognizing adhesive matrix molecules (MSCRAMMs). The distribution of these proteins is different among S. aureus isolates. In Iraq, there are no previous studies have been done in regard of distribution of these important virulence factors. Therefore, this study was designed to use PCR for screening of MSCRAMMs genes among local S. aureus isolates and determination of some virulence factors. S. aureus isolates (32) were collected from different hospitals in Baghdad and were diagnosed by conventional methods (cultural methods, colony morphology, Gram stain and biochemical tests). API Staph. System was used to confirm the diagnosis. Antimicrobial susceptibility test was performed by disc diffusion method for ten antibiotics. The ability to produce some virulence factors by bacterial isolated was detected [hemolysis activity, Deoxy ribonuclease (DNase) production and biofilm production]. The diagnosis of bacterial isolates was super-confirmed using PCR to detect the nuc gene. Uniplex and multiplex PCR were used to detect the MSCRAMMs genes (Uniplex PCR was used to detect fnbA and cna genes (each alone). multiplex PCR were used to detect bbp and ebp genes in one run and clfA, clfB, fib and fnbB genes in other run. All isolates were diagnosed as S. aureus (were negative to oxidase. Positive to catalase, slide and tube coagulase and Ferment mannitol). All isolates were recorded as S. aureus by API Staph system. A high prevalence of MRSA strains (78 %) was detected, vancomycin and imipenem were the most affected with percentage (97 %) and (94 %) respectively; results of susceptibility to other antibiotics was variant. Beta hemolysis was detected in (65.6 %) of isolates, 34.4% of isolates did not give any zone (gamma hemolysis), while no alpha hemolysis have been detected. On the other hand, all isolates (100%) produced DNase enzyme. The results of biofilm production assay shown that 40.6% of strains gave a weak positive results. The results shown that all isolates (100%) that were diagnosed as S. aureus by traditional methods harbored the nuc gene. The distribution percentage of bbp, ebp, clfA, clfB, cna, fib, fnbA and fnbB were 21.9%, 90.6%, 100%, 81.3%, 93.8%, 96.9%, 100% and 25% respectively. The distribution of adhesive genes are variant among S. aureus isolates and the infection sources. The bbp is the most specific infection associated gene with osteomyelitis.